2006
DOI: 10.1021/tx060157q
|View full text |Cite
|
Sign up to set email alerts
|

Pro-Oxidant Activity of Flavonoids Induces EpRE-Mediated Gene Expression

Abstract: Flavonoids are important bioactive dietary compounds. They induce electrophile-responsive element (EpRE)-mediated expression of enzymes, such as NAD(P)H-quinone oxidoreductase (NQO1) and glutathione S-transferases (GSTs), which are major defense enzymes against electrophilic toxicants and oxidative stress. The induction of EpRE-mediated gene transcription involves the release of the transcription factor Nrf2 from a complex with Keap1, either by a direct interaction of the inducer with Keap1 or by protein kinas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
124
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(141 citation statements)
references
References 49 publications
15
124
0
2
Order By: Relevance
“…Statistically speaking, the uric acid values remain significantly high both in the AHT group, and in the AHT + PA group in comparison with control group (Figure 2). The ability of dietary polyphenols to generate both NO and ROS in endothelial cells and activate ARE/EpRE (Antioxidant response element/Electrophile response element) mediated gene expression underlies their cardioprotective properties [6].…”
Section: Resultsmentioning
confidence: 99%
“…Statistically speaking, the uric acid values remain significantly high both in the AHT group, and in the AHT + PA group in comparison with control group (Figure 2). The ability of dietary polyphenols to generate both NO and ROS in endothelial cells and activate ARE/EpRE (Antioxidant response element/Electrophile response element) mediated gene expression underlies their cardioprotective properties [6].…”
Section: Resultsmentioning
confidence: 99%
“…Our results showed that ROS significantly induced the activation of Nrf2, and TV treatment increased nuclear localization of Nrf2, resulting in the enhanced production of antioxidants, such as HO‐1 and NQO‐1. The mechanism of TV activated Nrf2 may belongs to the polyphenols disrupt the Keap1‐Nrf2 complex, probably through interaction with the thiols present on Keap1 44. However, the mechanism of TV modified the Keap1‐Nrf2 complex remain open that need further investigation to confirm.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the addition of purified flavonoids to the diet could increase tissue and circulating total glutathione concentrations after prolonged administration and to some extent support the studies of Carlsen et al [24] in cultured HEP G2 cells. The increase in glutathione concentrations may be related to the role of this thiol in the detoxification of the electrophiles and free radicals; [25,26] these functions of glutathione have been recently reviewed by Pastore et al [27] Glutathione peroxidase is an antioxidant seleno-enzyme (found in most tissues) that reduces hydrogen peroxide and alkyl peroxide in tissues and uses glutathione as an essential redox substrate. Previous studies have shown that glutathione peroxidase activity is influenced by pesticide exposure.…”
Section: Discussionmentioning
confidence: 99%